Patterns of indigenous female cattle morphometric traits variations in Uganda: Evidence for farmers' selection to enhance agro-ecological fitness. (2nd February 2015) - Kabi, F.; Masembe, C.; Negrini, R.; Muwanika, V.
Summary: Globally, rural cattle keeping communities actively select and breed indigenous cattle to satisfy their interests and enhance adaptation to local landscapes. This study investigated how traditional systems in Uganda have shaped the morphometric population structure of indigenous cattle breeds. Ten linear morphometric traits were interrogated amongst 801 female cattle, comprising 46 Nganda ( Bos indicus ), 368 Ankole ( B. taurus indicus ) and 387 East African shorthorn zebu (EASZ, B. indicus ). The study cattle were obtained evenly at random from 209 herds in their agro-ecological zones (AEZs) where they have been nurtured by traditional cattle keeping communities throughout Uganda. Age, AEZs and breed significantly influenced the variation of linear morphometric traits exhibiting a gradient of low, intermediate and high dimensions among the EASZ, Nganda and Ankole cattle, respectively. Likewise, the linear morphometric trait (Mahalanobis squared distance) diversity was significantly different exhibiting a gradient of low, intermediate and high variation between Nganda and EASZ, Ankole and Nganda, and Ankole and EASZ cattle, respectively. These findings demonstrate the role of agro-ecological fitness in the evolution of indigenous cattle morphometric population structure in Uganda. The study outcomes further provide a motivation to search for genes associated with the diverse morphometric features. Résumé: Globalement, le bétail rurales en gardant les communautés sélectionner activement et élèvent du bétail autochtones à satisfaire leurs intérêts et améliorer l'adaptation aux paysages locaux. Cette étude a examiné comment les systèmes traditionnels en Ouganda ont façonné la structure de la population morphométrique des races bovines autochtones. Dix traits morphométriques linéaires ont été interrogés entre 801 bovins femelles, comprenant 46 Nganda (Bos indicus), 368 Ankole (B. taurus indicus) et 387 East African Shorthorn Zébu (EASZ, B. indicus. Les bovins de l'étude ont été obtenus uniformément au hasard à partir de 209 troupeaux dans leurs zones agro-écologiques (ZAE) où ils ont été nourris par l'élevage traditionnel de maintien de communautés à travers l'Ouganda. Âge, ZAE et élever significativement influencé la variation de traits morphométriques linéaires présentant un gradient de dimensions faibles, intermédiaires et élevés chez les EASZ, Nganda et Ankole bétail respectivement. De même, le caractère linéaire morphométrique (Mahalanobis distance au carré) la diversité est significativement différente présentant un gradient de faible, moyenne et forte variation entre Nganda et EASZ, Ankole et Nganda, Ankole et bétail EASZ respectivement. Ces résultats démontrent le rôle de remise en forme agro- écologique dans l'évolution de la structure de la population des bovins morphométrique indigène en Ouganda . Les résultats fournissent en outre une motivation à rechercher des gènes liés aux caractéristiques morphométriques diverses. Resumen: En todos los países del Mundo, las comunidades rurales de ganaderos seleccionan activamente y crían el ganado bovino autóctono con el fin de satisfacer sus intereses y de mejorar la adaptación al entorno local. Este estudio pretendió determinar de qué manera los sistemas tradicionales han conformado, en Uganda, la estructura morfométrica de la población de razas bovinas autóctonas. Se midieron diez rasgos morfométricos lineales en 801 hembras de ganado bovino, entre las cuales 46 de raza Nganda ( Bos indicus ), 368 de raza Ankole ( B. taurus indicus ) y 387 de Cebú de Cuernos Cortos del Este de África (EASZ por sus siglas en inglés, B. indicus ). Los animales del estudio fueron tomados, por toda Uganda, equitativamente y al azar, de 209 rebaños, en las zonas agroecológicas en las que habían sido criados por comunidades tradicionales de ganaderos. La edad, la zona agroecológica y la raza influyeron significativamente sobre la variación de los rasgos morfométricos lineales, mostrando un gradiente de bajo, intermedio y alto en las medidas para el ganado EASZ, Nganda y Ankole, respectivamente. Asimismo, la diversidad en los rasgos morfométricos lineales (distancia cuadrática de Mahalanobis) difirió significativamente, mostrando un gradiente de bajo, intermedio y alto para la variación entre Nganda y EASZ, entre Ankole y Nganda y entre Ankole y EASZ, respectivamente. Estos resultados demuestran el papel de la adaptación a la zona agroecológica en la evolución de la estructura morfométrica de la población de ganado bovino autóctono en Uganda. Lo hallado en este estudio anima a buscar los genes asociados con las diversas características morfométricas.